MUSIK BECANANG DALAM MALAM ADAT BEGURU PADA MASYARAKAT GAYO KECAMATAN BEBESEN, KABUPATEN ACEH TENGAH (Kajian terhadap bentuk penyajian dan bentuk musik) - Dara Arigustika (Universitas Negeri Medan, 2017)
Becanang Traditional Music In The EveningBeguru in Gayo Society Bebesen Districts, District Central Aceh (Study of the form ofpresentation and form of music). Faculty Of Language and Art. Medan State University,2015.This research is a study about the existence of the forms of presentation becanangmusic and music form becanang the Gayo people in the District of Central Aceh DistrictBebesen. The purpose of this study was to determine the presence of music in the districtbecanang Bebesen, form of presentation and form of music in the evening becanangbeguru indigenous community in the district of Gayo Bebesen, District Central Aceh.Thisresearch is based on theoretical foundation to explain the meaning of existence,understanding forms of presentation, understanding forms of music, understanding nightbecanang indigenous communities beguru Gayo. The method in this study used aqualitative descriptive method. The sample in this study is penatuah customaryunderstanding of the cultural traditions of indigenous communities which are also GayoGayo people of Central Aceh district. This data collection is done by the method ofobservation, interviews, laboratory work and literature study. This study was taken at thesite of the District Bebesen, Central Aceh district and the research was conducted fromJune 2015 through to August 2015. The results showed that the presence in the districtBebesen becanang music still plays an important role in any wedding processionindigenous Gayo people which can be seen from its function, especially in the traditionalevening event Beguru to be a communication tool and as a sign that Beguru event tobegin. Form of presentation of music becanang played with several musical instrumentstradition and consists of Gegedem, cymbals, Memong and gong, music becanang has avery important role in every stage of the traditional events marriage Gayo society,especially on the eve of indigenous Beguru as a communication tool caller localcommunities and as a sign that the traditional evening Beguru begin. Becanang musicalform only play three different forms of rhythm alone, three rhythm is played in alternatingturns, the most prominent bring rhythm motif is gegedem, on Memong instruments,cymbals and gongs just follow it, cymbals used as a regulator of tempo.